Analisis Dampak Gempa Bumi terhadap Pelayanan PDAM pada Pekerjaan Produktif di Sungai Lareh dan Pasir Nan Tigo - Rika Septrizarty (SAFE-Network, 2023)
Water is the main of people need because human can not survive without water. People need water to do reproductive work and productive purpose. The earthquake that happened in Padang City, September 30th 2009 damaged the facilities of Water Resource Agency. It was observed that the 7,6 RS Padang earthquake changed degradation on water resources utilized by farming household and sea fishery household. As survival efforts, farming household and sea fishery household set up adaption on such matters. This study aims to analyze the impacts of earthquake on th e service of PDAM (the firm of govenrment water agency) Padang City on farming household and sea fishery household. These villages are located in the same district, Koto Tangah. Fifteen women and fifteen men in each village were interviewed by in-depth interview with total 60 respondents. By using tabulation, graph it can conclude that earthquake as one of natural disaster gave different impacts on different community. In this case, sea fishery household in Pasir Nan Tigo was more vulnerable than farming household in Sungai Lareh for productive work.